2018
DOI: 10.3897/evolsyst.2.22678
|View full text |Cite
|
Sign up to set email alerts
|

Nano-indentation of native phytoliths and dental tissues: implications for herbivore-plant combat and dental wear proxies

Abstract: Tooth wear induced by abrasive particles is a key process affecting dental function and life expectancy in mammals. Abrasive particles may be plant endogenous opal phytoliths, exogene wind-blown quartz dust or rain borne mineral particles ingested by mammals. Nano-indentation hardness of abrasive particles and dental tissues is a significant yet not fully established parameter of this tribological system. We provide consistent nano-indentation hardness data for some of the major antagonists in the dental tribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Thus, the inherent structural properties of the grass blades or their abrasiveness was changed by drying, even though they became more brittle and should fracture more easily. A recent study (37) suggests that phytolith characteristics depend on the extraction method, with native phytoliths showing lower indentation hardness than phytoliths extracted by dry ashing. Consequently, the dehydration of plant tissues could have altered the hardness of phytoliths and led to more abrasion in the dry grass group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the inherent structural properties of the grass blades or their abrasiveness was changed by drying, even though they became more brittle and should fracture more easily. A recent study (37) suggests that phytolith characteristics depend on the extraction method, with native phytoliths showing lower indentation hardness than phytoliths extracted by dry ashing. Consequently, the dehydration of plant tissues could have altered the hardness of phytoliths and led to more abrasion in the dry grass group.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, internal abrasives, namely opal phytoliths [amorphous silica bodies with complex ultrastructural patterns (30)], have long been suggested as the causal agents of the scratch-dominated tooth wear characteristic of grazers (3133). Recent studies, however, produced equivocal results on whether phytoliths can actually scratch enamel (3437). On the other hand, grazing is associated with feeding close to the ground and often also with seasonally arid and hence dusty grassland environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Type of Abrasive Particles. It is well known that quartz (crystalline SiO 2 , Mohs hardness: 7) is harder than dental enamel (apatite, Mohs hardness: 5) both on Mohs hardness scale and in indentation tests (6,7,13,51,52). Consequently, quartz-containing grit and mineral dust have long been suggested as the main abrasive agents of dental wear (3,(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
“…Controlled feeding experiments with small mammals have shown that phytoliths, even though these endogenous plant silica bodies of 10 up to 100 μm are softer than dental enamel (13), cause distinct dental microwear texture (DMT) patterns (14) and that phytolith-rich diets lead to more dental (macro-)wear than phytolith-poor diets (9,10,15). For exogenous grit and/or mineral dust, however, controlled feeding experiments have produced ambiguous results.…”
mentioning
confidence: 99%